Preoperative myocardial troponin T elevation is associated with the fracture type in patients with proximal femoral fracture. (December 2019) - Nordling, P.; Strandberg, M.; Strandberg, N. N. G.; Kiviniemi, T. O.; Mäkelä, K. T.; Airaksinen, K. E. J.
Background and Aims: Cardiovascular complications are common in hip fracture patients but the role of fracture type and operative method in these is unclear. This prospective cohort study aimed to evaluate the impact of fracture- and operative characteristics on perioperative cardiovascular complications and prognosis in unselected hip fracture patients. Material and Methods: During a 7-month trial registration period, a population of 197 consecutive hip fracture patients (median age 84 years) diagnosed with femoral neck or pertrochanteric fracture was formed. The exclusion criteria were patient refusal, subtrochanteric fracture, or death preoperatively. Pre- and postoperative troponin T (TnT) elevation, perioperative N-terminal fragment of pro-B-type natriuretic peptide (NT-proBNP) level, perioperative cardiovascular adverse events, and all-cause 30-day and 2- and 5-year mortalities were studied. Results: Femoral neck fracture was independently associated with preoperative myocardial injury witnessed by TnT elevation (HR 2.95, 95% confidence interval 1.21–7.19, p = 0.018). The fracture type, surgery delay, or operative method were not significantly associated with NT-proBNP levels, cardiovascular adverse event diagnoses, or prognosis. Cardiovascular adverse events were clinically diagnosed in 28 (14%) participants, and these had a higher mortality compared to participants without such diagnosis (at 30 days, 32% vs 5%; 2 years, 71% vs 31%; and 5 years, 86% vs 59%; p < 0.001). Conclusion: While the femoral neck fracture independently predicts preoperative cardiovascular morbidity, the operative method does not affect perioperative cardiovascular complications or the prognosis, and it may be selected by the treating clinician based on other criteria.